Integrating pinch analysis and process simulation within equation-oriented simulators. (2nd November 2019) - Elias, Andrew Milli; Giordano, Roberto de Campos; Secchi, Argimiro Resende; Furlan, Felipe Fernando
Highlights: Pinch analysis integrated to equation-oriented simulator for process synthesis. Pinch analysis provides economically near optimal heat integration solutions. Process simulation robustness improved through heat integration by pinch analysis. Abstract: Process integration techniques may increase productivity and profitability while, at the same time, reducing environmental impacts. In this work, pinch analysis (one of the most popular energy-integration methodologies) was integrated into an equation-oriented simulator, providing energy integration in simulation time, without an external convergence loop. Based on four case studies, pinch analysis was showed to overestimate the optimal total annual cost within a maximum deviation of 10.7%, compared to superstructure-based optimization approaches, providing a near-optimal solution. This is well suited for the initial stages of process synthesis, where only rough estimates of process costs are sought. The methodology was also applied to a bioethanol biorefinery, containing more than 27, 000 variables. Energy integration reduced steam consumption by up to 12.8%, increasing plant productivity. An additional advantage of the integrated pinch analysis is that it increased the robustness to the process simulation, by replacing heat exchangers by the pinch formulae.